Spatiotemporal Variability of Air Stagnation and its Relation to Summertime Ozone in the Yangtze River Delta of China - Xie, Min; Zhan, Chenchao; Zhan, Yangzhihao; Shi, Jie; Luo, Yi; Zhang, Ming; Liu, Qian; Shen, Fanhui (Frontiers in Environmental Science, 2021)
This paper investigates the spatiotemporal variability of air stagnation in summer as well as its relation to summer ozone (O3) over the Yangtze River Delta (YRD) region of China. Air stagnation days (ASDs) in the YRD during the summers from 2001 to 2017 range from 9 to 54 days (9.2–58.4% of the entire summer days). With the empirical orthogonal function (EOF) analysis, the dominant weather systems affecting air stagnation in the YRD are illustrated. The first three EOFs explain 68.8, 11.3, and 7.1% of the total variance of ASDs, respectively. The first EOF represents the same phase of the entire YRD, which is attributed to the East Asian summer monsoon and mainly depends on the area and the intensity of the South China Sea subtropical high. The second EOF shows significant maritime-continental contrasts, which is related to stronger near-surface winds on sea. As for the third EOF, the air stagnation in the north and the south of the YRD has the opposite phase, with a dividing line along approximately 31°N. This spatial pattern depends on the area and the intensity of the northern hemisphere polar vortex that affects the meridional circulation. O3 is the typical air pollutant in hot seasons in the YRD. It is generally at a high pollution level in summer, and has a positive trend from 2013 to 2017. Air stagnation can affect O3 pollution levels in the YRD. In ASDs, there are usually weak wind, less precipitation, low relative humidity, high temperature, strong solar radiation and high surface pressure, which are favorable to the formation of O3. More O3 pollution episodes in 2013 than 2015 can be partly attributed to more ASDs in 2013. These results show that stagnant meteorological state can lead to the hazardous air quality, and provide valuable insight into the effect of air stagnation on the changes in surface O3 during hot months.